Optimalisasi Peran Kader melalui Pelatihan Integrasi Layanan Primer di Kabupaten Sleman - Tri Siswati; Nugraheni Tri Lestari; Ismi Izaz Ainun Najmi; Yustiana Olfah; Idi Setiyobroto; Agus Sarwo Prayogi (CV. CENDIKIA JENIUS INDONESIA, 2025)
Strengthening the capacity of health cadres is a key element in supporting the transformation of primary health services in Indonesia. This activity aims to improve the knowledge and skills of Posyandu cadres in implementing Primary Service Integration (ILP) at the Sleman Health Center. The training was conducted in Nogotirto Village, Gamping, Sleman Regency, using a practice-based approach, which involved providing training materials, simulations, and evaluations before and after the training. This method is designed to improve cadres' knowledge and skills about primary service integration through hands-on experience in the field. Most of the cadres involved in the training are between 41-50 years old (64%), with a background in the housewife profession (80%), and have experience as cadres for 1-10 years (48%). This characteristic indicates that the trainees have sufficient expertise to understand the needs in the field, although they still need to strengthen the technical and managerial aspects. The training results showed an increase in the knowledge and skills of cadres by 42,1% and 32.1%, respectively. The most significant improvement was seen in the management skills of Posyandu and health services for adults and the elderly, by 35.7% each. However, challenges are still found, especially in simple technology-based recording and reporting, as well as the need to improve skills in every aspect, including Posyandu management, health services for infants and toddlers, school children and adolescents, pregnant and postpartum women, as well as adulthood and the elderly. Cadre capacity is important in improving the overall health status of the community, thereby contributing to the transformation of primary health services in Indonesia. To support the successful implementation of ILP, technical assistance is still needed so that the implementation of the program is in accordance with the guidelines that have been determined by the Ministry of Health.